Incredible rescue mission - Mian, Zanib (Mian, Zanib. Planet Omar, 2021)
"Omar is going on his biggest adventure yet--a trip to Pakistan! But his excitement about the trip is interrupted by some shocking news: his amazing teacher is not coming back to school, and no one will say why. When Omar and his friends start investigating, the hints they overhear and clues they find lead them to an alarming conclusion--it must be aliens! Omar has a huge imagination, but saving his teacher from aliens seems far-fetched even to him. He's going to need out-of-this-world creative thinking and a huge spirit of adventure to solve this mystery!"--